Utilization of the Banten Great Mosque Site as Learning Resource in History Subject in Class X in Class X SMAN 1 Pontang - Asmunah, Asmunah; Rustamana, Agus; Ribawati, Eko (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to determine the use of the Banten Grand Mosque site as a learning resource in history subjects in Class X of SMAN 1 Pontang. This type of research is descriptive qualitative. The data collection techniques used were interview, observation, documentation and questionnaire techniques. When the data was collected, data validity was tested using triangulation. The data technique used is the Miles & Huberman interactive model. The results of this research show that the use of the Banten Grand Mosque site as a learning resource was carried out well using the face-to-face method, in which there were three stages in the process, namely planning, implementation and evaluation. From this implementation, weaknesses were obtained both in planning and during implementation. Meanwhile, the advantages obtained are in both the cognitive and affective domains.